Penerapan metode interaktif dalam meningkatkan keaktifan siswa pada pembelajaran penjaskes - Hariadi Hariadi; Mahfuz Mahfuz; Rina Nopiana; Eko Saputra; M. Thuhir; Didik Daniyantara; Lalu Erpan Suryadi; Muh Muhtar Darmuliyono; Muh. Syamsul Arifin Hafiz; Paozan Azima (Universitas Hamzanwadi, 2023)
This study aims to determine the effect of the application of interactive methods in increasing student activeness in physical education learning. The research method used is descriptive method in the form of written or spoken words from the person observed. This research was conducted at Madrasah Aliyah Asy-Syafi'iyah Bendung, the subjects of this research were sports teachers and students of class XI IPA Ma Asy-Syafi'iyah Bendung. There are two sources of data used, namely primary data sources are data directly collected by researchers from statements submitted to sources, namely sports teachers and also students of class XI IPA Ma Asy-Syafi'iyah Bendung in the form of observation, interviews, and documentation. Secondary data sources are data directly collected by researchers through articles and journals. The results of the research obtained by the researcher that the interactive method is able to make students become more active in the learning process, seen from before and after the provision of game-based interactive methods students become more excited and do not feel bored in the learning process. It can be concluded that student learning outcomes in PE subjects taught using game-based interactive methods can increase student activeness in the PE learning process.